Graph theory and its applications - Gross, Jonathan L. (Discrete mathematics and its applications., 2006)
"Interest in graphs and their applications continues to grow rapidly. Already an international bestseller, with the release of this second edition, Graph Theory and Its Applications is now an even better choice for formal course work, for self-study, and for reference." "The superior explanations, broad coverage, and abundance of illustrations and exercises that positioned this as the premier graph theory text remain, but are now augmented by a broad range of improvements. Nearly 200 pages have been added for this edition, including nine new sections and hundreds of new exercises, mostly non-routine."--BOOK JACKET.